Detroit Area Study, 1983: Attitudes and Experiences in Detroit - Hasenfeld, Yeheskel ([Verlag nicht ermittelbar], 1990)
This Detroit Area Study explored views on welfare as well as contact and experiences with government welfare agencies. The survey sought opinions on a gamut of welfare issues such as the level of government spending on Aid for Dependent Children, unemployment benefits, social security and food stamps, government aid to minorities and to communities losing industrial plants, whether government aid to the poor tends to make people lazy and dependent or helps to reduce crime and urban unrest, whether farmers, veterans, and home-owners were deserving of government aid or tax relief, and whether the government should guarantee everyone a minimum income or provide medical care or college tuition to the needy or to everyone as a matter of right. Respondents were asked to report on their encounters with public welfare agencies, including reasons for the contact, number of contacts during the last year, pre-contact expectations about services that would be received, whether or not needed services were actually obtained, and satisfaction with the way their requests were handled. Other items covered by the survey are political identification, vote in the 1980 presidential elections, trust and confidence in the federal government, and opinions on waste and inefficiency in various federal government programs including protection of the environment and national defense. Additional information gathered by the survey includes number of children and adults residing in the household, household income and its sources, respondents' age, sex, race, marital status, religious preference, and income, and the education, employment status, occupation, and industry of respondents and their spouses.